2018
DOI: 10.1088/1361-6463/aac29b
|View full text |Cite
|
Sign up to set email alerts
|

Review of multi-layered magnetoelectric composite materials and devices applications

Abstract: Multiferroic materials with the coexistence of at least two ferroic orders, such as ferroelectricity, ferromagnetism, or ferroelasticity, have recently attracted ever-increasing attention due to their potential for multifunctional device applications, including magnetic and current sensors, energy harvesters, magnetoelectric (ME) random access memory and logic devices, tunable microwave devices, and ME antenna. In this article, we provide a review of the recent and ongoing research efforts in the field of mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
118
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 228 publications
(122 citation statements)
references
References 148 publications
1
118
0
3
Order By: Relevance
“…Conventionally, magnetic energy was harvested using electromagnetic devices using coils and magnets (Faraday's induction law) which have limitations related to frequency, size and efficiency [4,5]. Those limitations can be overcome through the designs of newly discovered magnetoelectric (ME) composite materials [5,6]. In the ME effect, the magnetic field induced magnetostrictive strain transferred to the piezoelectric layer across interface generates the electric polarization due to piezoelectric effect [5].…”
Section: Introductionmentioning
confidence: 99%
“…Conventionally, magnetic energy was harvested using electromagnetic devices using coils and magnets (Faraday's induction law) which have limitations related to frequency, size and efficiency [4,5]. Those limitations can be overcome through the designs of newly discovered magnetoelectric (ME) composite materials [5,6]. In the ME effect, the magnetic field induced magnetostrictive strain transferred to the piezoelectric layer across interface generates the electric polarization due to piezoelectric effect [5].…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9] Search-coil, as a conventional magnetic sensor, has a high magnetic sensitivity, and its detectable magnetic field is as low as 20 fT/Hz 1/2 at 1 kHz. [16][17][18][19][20][21][22][23] Compared with magnetic sensors mentioned above, the ME sensor shows great potential for weak magnetic detection due to its superhigh magnetic field sensitivity. And the search-coil is often limited to the detection for the alternating current magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…It also has the advantages of low cost, light weight, easy fabrication, and high magnetic directivity. [16,19,[27][28][29][30][31][32] However, the system-level application based on the ME sensor is still in an early stage, although some prototypes have been developed for different usage scenarios. Recently, Chu et al have reported a (1-1) type ME sensor with a 1D configuration.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations